Enhancing Social Media Engagement for Logistics Services Branding - Serbetçioğlu, Cemre (2023)
This study investigates logistics service providers' social media engagement to understand better its effect on supply chain functions, mainly their branding purposes, since managers and academics consider branding strategies increasingly crucial in the current competitive business environment. Eleven semi-structured in-depth interviews with thirteen social media experts from the selected logistics service providers operating in Turkey were conducted to understand their social media use better and identify their decision-making mechanisms. The theoretical analysis is based on the technology acceptance model and media synchronicity theory. The findings suggest that business-to-business and business-to-customer settings are distinct, while logistics sector companies differentiate themselves through social media branding strategies. The most significant drivers of social media engagement are creating brand recognition and brand awareness, while the main perceived barriers are regulations and stakeholder permission. DOI: https://doi.org/10.54663/2182-9306.2023.sn13.125-155